Pragmática da entonação: a relação prosódia/ contexto em atos diretivos no Português - Adriana Nascimento Bodolay (2009)
This study aims to present an analysis on the relationship between the use of prosodic parameters and directive speech acts of order and request in Brazilian Portuguese. SPERBER & WILSON (1995), HIRST (2005), WICHMANN (2005) show that the production of sense at the enunciation, does not depend on the lexical content, but a correlationbetween internal and external factors to the act of language. In order to show how these aspects, prosody, semantic information and contextual information, are linked, we propose in this work to investigate the directive acts, driven by the theory of speech acts (AUSTIN, 1990, SEARLE, 1981). As methodology, and to ensure the quality of the acoustic signal, we selected a corpus of data from the soap opera Belíssima, interacting with characters in different contexts. Data were collected by UHF antenna and recorded on DVD player. From the perspective of instrumental analysis, we chose the extraction ofthe curve of F0 and the extent of segmental duration, since the literature presents both as acoustic correlates that best represent the intonation. The results show a tendency to use two prosodic patterns for order and two for the request. In terms of total duration of the statement, the orders are smaller than the requests. There is a significant correlation,with regard to the use of illocutionary force according to the listener and a trend towards alignment of the F0 peak in the early part of the statements, both in order and request. As regards attitudes, we found that those related to politeness and courtesy often occur. We also propose a discussion on the acoustic parameters of pitch, which is measured inthe melodic curve, since only three points do not represent certain types of prosodic pattern.